Everything in its place : a story of books and belonging - David-Sax, Pauline (Doubleday Books for Young Readers, 2022)
"A shy girl who feels most at home in the school library gains the courage to extend herself to others when she encounters a group of unique, diverse, inspiring women at the diner where her mother works"--